Prenatal diagnosis of pygopagus tetrapus parasitic twin: case report - Ceylan Yavuz; Aslan Halil; Gul Ahmet (BMC, 2004)
Abstract Background Asymmetric and parasitic conjoined twins are rarer anomalies of monochorionic monoamniotic twins, consisting of an incomplete twin attached to the fully developed body of the co-twin. Case presentation A 30-year-old multigravid woman referred to maternal fetal unit due to polyhydramnios at 28th week of gestation. Sonographic examination revealed a single fetus and polyhydramnios with amniotic fluid index 30 cm. The fetus had normal apparent single head, spine, thorax, abdomen, two upper and two lower limbs, and two relatively well developed rudimentary parasitic lower limbs at sacral region. Lower limbs of the autosite were moving freelly but no movement was detected at the parasite. The parasite contained irregular lower limbs and left foot with three toes. Short and deformed long bones were also present in the parasitic limbs. A Cesarean section was performed at 38th week of gestation and a live female infant weighing 3600 g was delivered. The parasitic lower limbs were totally excised. Post-operative period was uneventful and the newborn was discharged as healthy. Post-natal follow-up was normal at nine-month-old. Conclusion Pygopagus tetrapus parasitic twin is a rare form of conjoined twins and in utero diagnosis with ultrasound assists in prenatal management and counselling with parents.